EFFECTIVENESS OF DIFFERENT METHODS AND APPROACHES IN TEACHING ENGLISH (Лучшие интеллектуальные исследования, 2024)
Annotation:  Language teaching approaches and methods have cast light on the language teaching theory and practice. There are still many controversies about their usefulness and appropriateness. This paper tries to analyze their effectiveness and weakness of several most influential teaching approaches and methods: Grammar-translation Method, Direct Method, Audio-lingual Method, Communicative Teaching Method, in order to have a better understanding and application in the future teaching practice .